Inhibition of epoxyeicosatrienoic acid production in rats with cirrhosis has beneficial effects on portal hypertension by reducing splanchnic vasodilation. Issue 3 (22nd July 2016) - Di Pascoli, Marco; Zampieri, Francesca; Verardo, Alberto; Pesce, Paola; Turato, Cristian; Angeli, Paolo; Sacerdoti, David; Bolognesi, Massimo
Abstract : In cirrhosis, 11, 12‐epoxyeicosatrienoic acid (EET) induces mesenteric arterial vasodilation, which contributes to the onset of portal hypertension. We evaluated the hemodynamic effects of in vivo inhibition of EET production in experimental cirrhosis. Sixteen control rats and 16 rats with carbon tetrachloride‐induced cirrhosis were studied. Eight controls and eight rats with cirrhosis were treated with the specific epoxygenase inhibitor N ‐(methylsulfonyl)‐2‐(2‐propynyloxy)‐benzenehexanamide (MS‐PPOH; 20 mg/kg/day) for 3 consecutive days. Portal blood flow and renal and splenic resistive indexes were calculated through echographic measurements, while portal and systemic pressures were measured through polyethylene−50 catheters. Small resistance mesenteric arteries were connected to a pressure servo controller in a video‐monitored perfusion system, and concentration‐response curves to phenylephrine and acetylcholine were evaluated. EET levels were measured in tissue homogenates of rat liver, kidney, and aorta, using an enzyme‐linked immunosorbent assay. Urinary Na + excretion function was also evaluated. In rats with cirrhosis, treatment with MS‐PPOH significantly reduced portal blood flow and portal pressure compared to vehicle (13.6 ± 5.7 versus 25.3 ± 7.1 mL/min/100 g body weight, P < 0.05; 9.6 ± 1.1 versus 12.2 ± 2.3 mm Hg, P < 0.05; respectively) without effects on systemic pressure. An increased response to acetylcholine of mesenteric arteries from rats with cirrhosis (50% effect concentration ‐7.083 ± 0.197 versus ‐6.517 ± 0.73 in control rats, P < 0.05) was reversed after inhibition of EET production (‐6.388 ± 0.263, P < 0.05). In liver, kidney, and aorta from animals with cirrhosis, treatment with MS‐PPOH reversed the increase in EET levels. In both controls and rats with cirrhosis, MS‐PPOH increased urinary Na + excretion. Conclusion : In rats with cirrhosis, in vivo inhibition of EET production normalizes the response of mesenteric arteries to vasodilators, with beneficial effects on portal hypertension. (Hepatology 2016;64:923‐930)